Hydrodynamic studies of a complex between the Fc fragment of human IgE and a soluble fragment of the Fc epsilon RI alpha chain. - Keown, M B (1995)
The interaction between immunoglobulin E (IgE) and its high-affinity receptor Fc epsilon RI is central to allergic disease. The binding site for Fc epsilon RI lies in the third constant region domain of the epsilon heavy chain of IgE (C epsilon 3). Identical epitopes on the two C epsilon 3 domains in the IgE-Fc are predicted to be on opposite sides of the structure, and therefore each could bind independently to a receptor molecule. Titrations, however, reveal that the IgE-Fc forms an equimolar complex with a soluble fragment of the Fc epsilon RI alpha chain (sFc epsilon RI alpha), and the molecular weight of the complex, as determined by sedimentation equilibrium, confirms this stoichiometry. The measured sedimentation coefficients of the two ligands are in good agreement with computed values for a compact IgE-Fc and an elongated sFc epsilon RI alpha structure. The calculated sedimentation coefficients for possible models of a 1:1 complex lead to exclusion of all highly extended geometries for the complex. Possible explanations for the paradoxical stoichiometry of the IgE-Fc/sFc epsilon RI alpha complex, in terms of the curved shape of IgE, a conformational change in IgE when the receptor binds, and steric interference between two molecules of Fc epsilon RI binding to identical sites, are discussed.